An Atypical Presentation of Extrapulmonary Sarcoidosis - Muhammad Shabbir Rawala; Amna Saleem Ahmed; Kristen Helmick (Case Reports in Rheumatology)
Sarcoidosis is an idiopathic, chronic, multisystem, granulomatous, inflammatory disease involving almost all organs. Sarcoidosis can occur with an atypical presentation of hepatosplenic involvement, like in the case of our patient. In this case report, we present a rare case of extrapulmonary sarcoidosis with isolated involvement of the liver and spleen in a 39-year-old Caucasian female. There is a possibility of this isolated involvement of an organ in the complete absence of pulmonary disease, which makes the diagnosis of sarcoidosis very difficult as it is usually not suspected. Ultrasound and CT are important in ruling out other differential diagnoses, but a definitive diagnosis is possible only on histological examination, differentiating sarcoid lesions from tuberculosis, primary biliary cirrhosis, metastasis, malignancy, and other granulomatous infections or diseases. Hence, the most credible criterion for diagnosis remains histology. After diagnosis, regular follow-up for systemic manifestations is recommended. Asymptomatic patients with hepatosplenic sarcoidosis have a good prognosis without any medical intervention, while patients with abnormal labs or symptoms must commence treatment.